ANIMATED EDUCATIONAL VIDEOS AND EFL LEARNERS’ FOREIGN LANGUAGE ANXIETY - Dira, Benito; Kuswandono, Paulus (UC Journal: ELT, Linguistics and Literature Journal, 2024)
Anxiety is known as foreign language anxiety when correlated to the learning of foreign languages. Animated educational videos can serve as excellent instruments for visually facilitating the courses. Although recent studies discussed the benefits of using video in educational activities and other similar subjects, only a few findings focused on the impact on EFL learners’ Foreign Language Anxiety. To provide a thorough description of the occurring phenomenon from the perspective of the research participants, the researchers used a qualitative approach. On the grounds of this, the researchers used convenience sampling as the preferred technique in collecting the sample, particularly comprehensive sampling. The research participants were 12 students of at the English Language Education Study Program (ELESP) of Sanata Dharma University. The data were collected through an online survey using an open-ended questionnaire and an online interview. The findings revealed that there were two results based on this research. First, the use of animated educational videos both increases anxiety and reduces anxiety. Nonetheless, it was also found that the animated educational videos did not boost nor decrease EFL learners' anxiety about foreign languages. Second, the researcher found that topic and video editing were the aspects that influenced the EFL learners.